2008
DOI: 10.1016/j.plasmid.2008.01.005
|View full text |Cite
|
Sign up to set email alerts
|

The complete sequence and functional analysis of pANL, the large plasmid of the unicellular freshwater cyanobacterium Synechococcus elongatus PCC 7942

Abstract: Two endogenous plasmids are present in Synechococcus elongatus PCC 7942, a model organism for studying photosynthesis and circadian rhythms in cyanobacteria. The large plasmid, pANL, was shown previously to be involved in adaptation of S. elongatus cells to sulfur starvation, which provided the first evidence of cellular function of a cyanobacterial plasmid. Here, we report the complete sequence of pANL, which is 46,366 bp in length with 53% GC content and encodes 58 putative ORFs. The pANL plasmid can be divi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 42 publications
0
34
0
Order By: Relevance
“…Surprisingly, the 46 kb pANL plasmid, which is extra-chromosomal in WT S. elongatus (Chen et al, 2008), was integrated into the ΔdnaA-1 and -2 chromosome at different sites, although there were no other mutations. Moreover, Southern blotting and capillary sequencing revealed that all pANL copies were integrated in the middle of the Syn7942_0826 gene in ΔdnaA-1 and in the intergenic region between Syn7942_1297 and Syn7942_1298 in ΔdnaA-2 (Figure 3 and Supplementary Figure S2), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Surprisingly, the 46 kb pANL plasmid, which is extra-chromosomal in WT S. elongatus (Chen et al, 2008), was integrated into the ΔdnaA-1 and -2 chromosome at different sites, although there were no other mutations. Moreover, Southern blotting and capillary sequencing revealed that all pANL copies were integrated in the middle of the Syn7942_0826 gene in ΔdnaA-1 and in the intergenic region between Syn7942_1297 and Syn7942_1298 in ΔdnaA-2 (Figure 3 and Supplementary Figure S2), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The 46.3-kb pANL plasmid, indigenous to Se7942, could potentially interfere with the conjugation or stability of other plasmids, hence our interest in attempting pANL plasmid curing. Several shuttle plasmids were built, all based on a 1,395-bp DNA segment containing pANL putative origin of replication (23). The replication region (here named rep_pANL) that was cloned to construct the pDEP vector series included an additional 18-bp fragment to complete the coding region of gene anL57 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In another attempt to remove pANL, regions named gap2 and gap3, described as essential in an earlier study (23), were incorporated into the dislodging vector, thus producing pDEP23 (see Fig. S2 in the supplemental material).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Its genome was sequenced, annotated and published in 1980 (van den Hondel et al, 1980;Van der Plas et al, 1992;Chen et al, 2008). Shastri and Morgan (2005), which leads to short-cuts in flux distributions when optimised.…”
Section: Synechococcus Elongatus Pcc 7942mentioning
confidence: 99%